Deep Learning for ship classification on medium resolution SAR imagery - Moujahid, Bou, Laouz; Rodolphe, Vadaine; Guillaume, Hajduch; Fablet, Ronan (HAL CCSD, 2023)
International audience This paper delves into the classification of vessels using medium-resolution SAR imagery from Sentinel-1, combined with AIS data streams. The study presents data considerations, a classification methodology, performance evaluation, and potential applications.